HIV transmission in sero-discordant couples with the HIV-positive partner in Xinjiang: incidence and associated predictors - Yongkang Ni; Xiaoyuan Hu; Zaoling Liu; Ning Tao; Yuanyuan Ma; Zhen Ni; Mingjian Ni (Journal of Infection in Developing Countries)
Introduction: To control the spread of human immunodeficiency virus (HIV) among sero-discordant couples, we explored the HIV seroconversion and its contributing factors.